A Randomized, Open‐Label, Phase I Clinical Study of Dalpiciclib With Different Specifications After Process Modification in Healthy Chinese Volunteers. Issue 1 (26th October 2022) - Tao, Ye; Li, Ting; Lin, Pingping; Jiang, Xin; Shi, Ping; Fu, Yao; Liu, Xin; Wang, Chenjing; Li, Shaorong; Li, Xiaofeng; Cao, Yu
Abstract: The purpose of this study was to determine the pharmacokinetic characteristics and safety of dalpiciclib at 100‐, 125‐, and 150‐mg doses after process modification in healthy Chinese volunteers. This single‐center, randomized, open‐label, three‐dose, phase I clinical study was conducted in healthy Chinese adults. Thirty‐six volunteers were randomized to three groups, including groups administered 100, 125, and 150 mg of dalpiciclib, and each group contained an equal number of males and females. A single oral dose of dalpiciclib was administered to each group, and plasma concentrations were measured by a validated liquid chromatography‐tandem mass spectrometry method. The oral formulation of dalpiciclib was well absorbed, the plasma concentration reached the maximum concentration (Cmax ) in 4–6 hours, and it was eliminated from plasma with a mean terminal half‐life of 42.9–45.5 hours after 100–150 mg was administered. Dalpiciclib exhibited safety and favorable pharmacokinetic profiles, supporting further investigations in phase II studies. The plasma exposure of dalpiciclib was dose‐dependent, with increasing doses in the range of 100–150 mg.